Comparison of Escherichia coli and Proteus mirabilis in patients infected with chronic pyelonephritis in Al-Najaf Governorate, Iraq - Rahman Abed Al-janabi Dhafer; Abduljabbar Jaloob Aljanaby Ahmed (BIO Web of Conferences)
Escherichia coli and Proteus mirabilis are two of the most common causes of upper or lowermurinary tract infection. The purpose of this study was to compare demographic characteristics and antimicrobial susceptibility of chronic pyelonephritis (CPN) between E. coli and P. mirabilis, and conducted by taking clinical samples urine from 288 patients with chronic pyelonephritis, including females and males, aged between 10-84 years, who attended Hospital Al-Sadr Teaching Urology Department in Najaf Governorate, Iraq from February 2023 to January 2024. The results showed that 17/288 (6%) were mix growth and 271/288 (94%) were single growths, which were focused on in this study (monomicrobe). The Gram-negative bacteria were 231/271 (85%) and the Gram-positive bacteria were 40/271 (15%), and E. coli bacteria constituted 119/231 (51.5%) and P. mirabilis, bacteria 27/231 (11.7%). The average ages were (52.92 ± 17.46) and (56.78 ± 18.03) for E. coli and P. mirabilis, bacteria, respectively. Significant differences were found at P-Value 0.5 in some age groups, in addition to both bacteria in males more prevalent with a significant difference. The presence of E. coli bacteria was more widespread in urban areas, unlike bacteria. P. mirabilis, which was more widespread in rural areas. Ten antibiotics were tested to compare them, and there were four antibiotics, namely Augmentin, Amikacin, Trimethoprim and Imipenem, which had the same effect and did not constitute any significant difference. As for the other types, they formed a significant difference.